Sistem Pendukung Keputusan Untuk Mendiagnosis Penyakit Psikofisiologis - Arnika, Qurniah Ulfahsari Putri, Nurgiyatna, S.T., M.Sc., Ph.D (2015)
Psychophysiological disease is a disorder in development caused by two things: the disruption caused by the physical and emotional state or psychological state. The process of early detection and understanding of psychophysiological disease is still lacking in the majority of ordinary people, even the blind can be classified information in the field of mental health. In this case, the need for rapid and precise information on health care or mental health specialist is needed for early detection. Therefore, solutions are needed as well as the dissemination of information about the disease through web technology. Implementation of these solutions is a decision support system for diagnosing psychophysiological diseases. In the search process, the method used is the method of approach that uses a forward chaining rule-based reasoning rule based reasoning. This study resulted in a decision support system for diagnosing disease based psychophysiological web will show that the system can help support the doctor's decision, also can determine the likelihood that a patient suffering from a disease or disorder according to the inputted symptoms, and can display the solution of the disease.